Face-centered-cubic to body-centered-cubic phase transformation of Cu nanoplate under [100] tensile loading. Issue 20 (18th October 2019) - Yu, Jiayun; Xie, Hongxian; Yin, Fuxing; Yu, Tao
ABSTRACT: Molecular dynamics simulation was used to stretch Cu nanoplates along its [100] direction at various strain rates and temperatures. Under high strain rate and beyond the elastic limit, the Cu nanoplates underwent an unusual deformation mechanism with expansion along free surface lateral direction and contraction along the other lateral direction, which leaded to the face-centred-cubic phase transforming into unstressed body-centred-cubic phase. Under low strain rate, the deformation of the nanoplate went back to well-known dislocation mechanism. The face-centred-cubic to body-centred-cubic phase transformation mechanism was further discussed in terms of elastic stability theory and free surface stress effect.